MORE FLORET1 Encodes a MYB Transcription Factor That Regulates Spikelet Development in Rice - Ren, Deyong (Plant Physiol, 2020)
Rice (Oryza sativa) spikelets have a unique inflorescence structure, and the mechanisms regulating their development are not yet fully understood. Moreover, approaches to manipulate spikelet development have the potential to increase grain yield. In this study, we identified and characterized a recessive spikelet mutant, namely more floret1 (mof1). The mof1 mutant has a delayed transition from the spikelet to the floral meristem, inducing the formation of extra lemma-like and palea-like organs. In addition, the main body of the palea was reduced, and the sterile lemma was enlarged and partially acquired hull (lemma and/or palea) identity. We used map-based cloning to identify the MOF1 locus and confirmed our identification by complementation and by generating new mof1 alleles using CRISPR-Cas9 gene editing. MOF1 encodes a MYB domain protein with the typical ethylene response factor-associated amphiphilic repression motifs, is expressed in all organs and tissues, and has a strong repression effect. MOF1 localizes to the nucleus and interacts with TOPLESS-RELATED PROTEINs to possibly repress the expression of downstream target genes. Taken together, our results reveal that MOF1 plays an important role in the regulation of organ identity and spikelet determinacy in rice.